Design and evaluation of piezoelectric response in a device based on liquid-phase exfoliated MoS2 (2019)
Two-dimensional materials have attracted much interest in the last years mainly because when quantum confinement is in place new properties appear. That is the case of single layer or odd layers of MoS2. When confined to 2 dimensions, MoS2 presents new properties, this change is due in part by the loss of centrosymmetry. Additionally, second-order responses appear like second-harmonic generation and piezoelectricity, in the case of MoS2.Then is essential to characterize this type of material in its 2D forms. Our study shows a way to deposit MoS2 using spray coating, and with this process we can study the topology of the MoS2 flakes; we also see the preferred way in which the MoS2 stacks. Two materials were studied, graphene and PMMA, as a possible energy transductor, for piezoelectric measurements, and it was found that in the current configuration graphene does not work as a transductor, and there is need to do further investigation on the PMMA